Simulasi Aliran Daya Pada Pembangkitan PLTBG 1 MW Di Laboratorium Teknik Listrik Dengan Koneksi PLN Penyulang RA.01 Rantau Prapat Menggunakan Software Electric Transient And Analysis Program (Etap) 12.6.0 - Wahyuni, Kanthi; Thamrin, Nj.; Dewi, Rozlinda (Universitas Batanghari Jambi, 2023)
PT Pangkatan Indonesia is an oil palm plantation company operating in Labuhanbatu Regency, North Sumatra Province, with a plantation area of 7,134.8 ha and has built a palm oil mill with an installed capacity of 40 tons / hour. Liquid waste from the plant has the potential to be an alternative source of raw materials for Biogas Power Plants (PLTBg) which is also a distributed generation (DG). The parameters to be studied in this study are the decrease in power losses and the voltage profile of the electrical power produced. The simulation process produces voltage under normal conditions, which only increases about 0.3% of the nominal voltage (complies with Ministerial Regulation No. 4 of 2009). In addition, the results of interconnection analysis at the 1 MW PLTBG show that the voltage at the ends before and after the connection has increased. Furthermore, the ratio of the total current before and after (load 75% - 95% ) is fixed (no change). The conclusion of the results of this study is, the greater the load, the greater the power produced.